(untitled) (Al Mustansiriyah Journal of Pharmaceutical Sciences, 2022)
Though chemotherapy is the major strategy to manage patients with advanced-stage colorectal cancer (CRC), the main challenge is the progression of CRC despite using combination of different chemotherapeutic agents. So, to overcome this challenge, a new class Of therapy was developed naming “Targeted-therapy”. This class of drugs aim to target specific overexpressed or aberrant enzyme, receptor, or gene that have critical role in the growth and survival of colorectal cancerous cells. So that, by using combination of traditional strategy (chemotherapy) and targeted-drug, this will lead to improve survival and prevent the progression of advanced CRC